Effects of plyometric jump training versus power training using free weights on measures of physical fitness in youth male soccer players - Sammoud, S.; Bouguezzi, R.; Ramirez-Campillo, R.; Negra, Y.; Prieske, O.; Moran, J.; Chaabene, H. (Journal of Sports Sciences, 2022)
This study aimed to contrast the effects of power training (PT) and plyometric-jump-training (PJT) programmes on measures of physical fitness in prepubertal male soccer players. Thirty-three participants were randomly allocated to PT group (n = 11), PJT group (n = 11), and an active control group (CG; n = 11). Before and after 12 weeks of training, tests were performed for the assessment of sprint-speed , change-of-direction (CoD) speed, muscular strength , and aerobic-endurance (AE). Findings indicated significant group×time interaction effects for all sprint-speed intervals, CoD speed, AE, and strength (d = 0.20-0.32). Post-hoc analyses revealed significant, moderate-to-large improvements in all sprint-speed intervals, CoD speed, AE, and muscle strength following PT (ES = 0.71 to 1.38). The PJT induced significant, moderate-to-large enhancements in 10 m, 20 m, and 30 m sprint, CoD speed, and AE (ES = 0.51 to 0.96) with no significant changes for 5 m sprint-speed and muscle strength (ES = 0.71 and 0.16, respectively). No significant pre-post changes were observed for the CG . Overall, PT and PJT are effective means to improve various measures of physical fitness in prepubertal male soccer players. Notably, to additionally improve acceleration and muscle strength, PT has an advantage over PJT.